2018
DOI: 10.1007/s11433-018-9202-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of bend loss in writing of three-dimensional optical waveguides with femtosecond laser pulses

Abstract: We provide a solution toward compact and low-loss three dimensional (3D) photonic circuits by femtosecond laser direct writing of 3D waveguides in fused silica. We suppress the bend loss by sandwiching the waveguide between a pair of walls formed by internal modification of glass. Our method allows to reduce the bend loss of a curved waveguide with a bending radius of 15 mm by more than one order of magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, the intensities of the resonant peaks do not match well due to the insufficient light confinement of the waveguide. This issue could be solved by adding suppression walls [35] beside the waveguide or increasing the index contrast [36], aiming to improve the light confinements within the BGWs.…”
Section: F Fabrication Of Bgws With Multiple Resonant Peaksmentioning
confidence: 99%
“…However, the intensities of the resonant peaks do not match well due to the insufficient light confinement of the waveguide. This issue could be solved by adding suppression walls [35] beside the waveguide or increasing the index contrast [36], aiming to improve the light confinements within the BGWs.…”
Section: F Fabrication Of Bgws With Multiple Resonant Peaksmentioning
confidence: 99%
“…In this work, both the waveguides and the modification tracks were fabricated using a home-built femtosecond laser direct writing setup [ 18 , 19 , 25 ]. A Ti: sapphire regenerative amplifier (LibraHE, Coherent Inc., Santa Clara, CA, USA) with an operation wavelength of 800 nm, a pulse width of 50 fs, and a repetition rate of 1 kHz was used as the writing laser source.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we provide an alternative solution to achieve smooth mode field compression in the waveguides written in glass. Our technique is based on a recent finding [ 25 ] that stress can be induced in the waveguides by writing two modification tracks in proximity to the waveguides using femtosecond laser direct writing. The stress can promote the refractive index change in the waveguide which gives rise to a significant reduction of the bend loss in the curved portion of the waveguide [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Liu et al [6] reported a technique which reduces the bending loss at small radii of curvatures by more than one order of magnitude. The key idea of their approach is shown in Figure 2.…”
mentioning
confidence: 99%